Strategi Pengembangan Agroindustri Karaginan Menggunakan Perspektif Keunggulan Bersaing Berkelanjutan - Yuli Wibowo (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
This paper describes application of fuzzy logic for predicting the competitiveness ofagroindustry of carrageenan and to develop strategy for enhancing it. Fuzzy expert system isused to predict the competitiveness using sustainable competitive advantage perspective withfour inputs, such as production amount, a place to compete, competitor, and customer service.Knowledge base management system is constructed using rule based production type, whereasinference mechanism is developed using Mamdani’s inference system. Matlab’s Fuzzy ToolboxVer 6.5 is used to design system implementation. Scenarios is constructed to improve thestrategy based on outputs of competitiveness using fuzzy analytical hierarchy process